Effectiveness of total knee arthroplasty rehabilitation programmes: A systematic review and meta-analysis - Waleed Alrawashdeh; Jörg Eschweiler; Filippo Migliorini; Yasser El Mansy; Markus Tingart; Björn Rath (Medical Journals Sweden, 2021)
Objective: To investigate the effectiveness of modified rehabilitation programmes in comparison with standard rehabilitation programmes after total knee arthroplasty through randomized controlled trials. Data sources: A search was conducted in PubMed, PubMed Central (PMC) and Cochrane Library databases in December 2020. Study selection: Randomized controlled trials were reviewed if they compared a physiotherapy exercise intervention with usual or standard physiotherapy care, or if they compared 2 types of exercise physiotherapy interventions meeting the review criteria, after total knee arthroplasty for osteoarthritis. A total of 18 randomized controlled trials were included at the end of the screening process. Data extraction: Two authors independently screened the literature, extracted data, and assessed the quality of included studies. The outcomes were knee extension, knee flexion, pain visual analogue scale, overall Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), 6-minute walking test, and Timed Up and Go test. Data synthesis: There was no clear pattern regarding which combination of starting time-point and duration of the rehabilitation programme after total knee arthroplasty significantly improves the clinical outcome when comparing modified rehabilitation programmes with standard programmes. Moreover, no particular modification to the modified programmes could be solely attributed to the improved clinical outcome in the 2 studies that showed significant improvement. Conclusion: Modified rehabilitation programmes do not result in systematic improvement in clinical outcome over one-size-fits-all-approaches after total knee arthroplasty.